Traumatic brain injury: Studies on serum biomarkers for diagnosis and single nucleotide polymorphisms to predict outcome / Anada Raj Poovindran - Anada Raj, Poovindran (2015)
Traumatic brain injury (TBI) is an important cause of morbidity and mortality. The objectives of this study are to determine the links, if any, between selected single nucleotide polymorphisms (SNPs) with 6 month post-TBI outcome, and to identify serum protein biomarkers that may be utilized to detect and grade the severity of TBI. A cross sectional cohort of 205 hospitalized TBI patients was prospectively studied for the SNPs in the genes of the Apolipoprotein E (APOE) and its promoter region, Catechol-O-Methyl Transferase (COMT), Dopamine D2 receptor (DRD2), Dopamine D3 receptor (DRD3), Ciliary Neurotrophic Factor (CNTF), Brain Derived Neurotrophic Factor (BDNF) and Glial cell Derived Neurotrophic Factor (GDNF) using patients blood DNA. The Glasgow Coma Score on admission, and Glasgow Outcome Scale at six months were determined in this cohort and correlated with the findings. A standard iTRAQ protocol was used to identify potential serum protein markers using serum pools from a separate cohort of mild, moderate and severe cases of TBI. Potential peptide candidates were analyzed on a “5800 MALDI TOF/ TOF mass spectrometer” and identified using the “ProteinPilot 4.0” software. Our analysis showed that possession of at least one APOE ε4 allele (OR: 5.5, 95% CI: 2.8-10.7, p= 0.01), COMT AA genotype (OR: 18.6, 95% CI: 5.97-58.03, p= 0.01) or at least one CNTF A allele (OR: 3.7, 95% CI: 1.88-7.36, p= 0.01) were significantly associated with unfavorable outcome at 6 months post-TBI. In the logistic model, the GCS alone significantly predicted unfavorable outcome in our TBI cohort (R2 = 30.8, p=0.01). However, GCS paired with the status of APOE ε4 allele (R2 = 60.9; APOE ε4 allele- OR: 8.0, 95% CI: 3.6-18.0, p= 0.01; GCS- OR: 5.0, 95% CI: 2.7-9.1, p= 0.01), GCS paired with COMT AA genotype (R2 = 60.61; COMT AA genotype- OR: 18.96, 95% CI: 5.48-65.56, p= 0.01; GCS- OR: 3.95, 95% CI: 2.17-7.17, p= 0.01) or GCS paired iv with CNTF A allele (R2 = 46.15; CNTF A allele- OR: 4.55, 95% CI: 2.10-9.86, p= 0.01; GCS- OR: 4.28, 95% CI: 2.42-7.58, p= 0.01) were better predictors for unfavorable outcome compared with GCS alone. Unfavorable outcome after TBI was not associated with alleles of SNPs of the APOE promoter, DRD2 gene, DRD3 gene, BDNF gene and GDNF gene. We identified 7 biomarkers to be increased in all grades (mild, moderate and severe) of TBI. Two of these markers (“Serum Amyloid- A” and “C- Reactive Protein”) were markers for general injury and inflammation. Five markers appear to be specifically increased in TBI (“Leucine- Rich alpha- 2 Glycoprotein- 1”, “Lipopolysaccharide Binding Protein”, “Fibronectin”, “Vitronectin” and “Alpha- 1 antichymotrypsin”). “Apolipoprotein E” and “Zinc Alpha- 2 glycoprotein” were increased only in severe TBI. Conversely, “Gelsolin” was decreased in all grades of TBI, whereas, “Kininogen” was decreased in moderate and severe TBI. If validated, some or all of these protein markers may aid in the detection of TBI, including mild TBI, in conjunction with other conventional diagnostic methods. Our findings suggest that certain serum protein markers and SNPs may be useful to aid clinicians in the diagnosis and grading of TBI, and for prediction of post-TBI outcome, respectively.